Kajian Yuridis Normatif Terhadap Pengaturan Perlindungan Hukum Bagi Pekerja Migran Indonesia Berdasarkan Undang-Undang Nomor 18 Tahun 2017 - Liony Leontin Mongi; Johanis L. S. S. Polii; Nopesius Bawembang; Pinta N. S. Simamora (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
This study examines the legal framework and effectiveness of legal protection for Indonesian Migrant Workers (PMI) under Law Number 18 of 2017. The main issue addressed is the gap between a progressive normative framework and weak practical implementation. This research employs a normative juridical method with statutory, conceptual, and historical approaches, based on primary, secondary, and tertiary legal materials. The findings indicate that, normatively, Law No. 18 of 2017 adopts a human rights – based approach covering pre-deployment, placement, and post-deployment protection, and is broadly aligned with international standards, including the 1990 UN Convention and ILO instruments. However, its implementation remains ineffective due to weak supervision, institutional fragmentation, the prevalence of irregular migration, and limited access to legal protection in host countries. This study highlights a “normative–implementation gap,” emphasizing that effective protection depends not only on legal norms but also on institutional capacity, cross-sectoral coordination, and transnational protection mechanisms. Therefore, strengthening operational regulations, integrated supervision, and state capacity is essential to ensure effective protection of migrant workers.